Propofol effects over intracranial pressure waveform and cerebral hemodynamics: A case report (Research, Society and Development, 2024)
Introduction: Few reports have been dedicated on assessing cerebral hemodynamics (CH) and intracranial compliance (ICC) in non-primary neurological patients. Objective: The present study aims to observe the anesthetic influence of propofol on CH and ICC using noninvasive monitoring techniques in the immediate postoperative period. Methodology: This is a case report in which CH and ICC were assessed noninvasively using transcranial Doppler (TCD) and a skull deformation sensor (B4C) respectively, in the immediate postoperative period of a patient just after cardiac revascularization. After exclusion of volemic depletion, TCD and B4C parameters indicated reduction in cerebral blood flow what would be attributed to propofol infusion during surgery. After endovenous additional volume administration and arterial pressure elevation, TCD and B4C parameters improved. Final Considerations: It was possible observing cerebrovascular influences of propofol in the immediate postoperative period, by means of neurological ancillary techniques. Noninvasive neuromonitoring is a way to assess changes in brain physiology that may occur subtly and influence in non-primary neurological patients outcomes.